Assessment of toxic response of Lactuca sativa to compost extracted from agri-food waste - Diego Andr´es Zapata-Gonz´alez; Juan Manuel Trujillo-Gonz´alez; Marco Aurelio Torres-Mora; Daniel Gonz´alez-Santamaria; Raimundo Jim´enez-Ballesta (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: In this study, we aim to investigate the suitability of five samples of compost extracted at various concentrations by testing for their phytotoxic response on Lactuca sativa L. We analyze relevant parameters with regards to the quality of the compost. By doing this, we hope to contribute to the attainability of clean, high-value organic fertilizer from local food waste production. Method: We set up a mini composting pilot where raw materials were classified, chopped into bits, and finally mixed. They include residues of Solanum tuberosum (potatoes), Zea mays (corn), Musa Paradisiaca (bananas), Allium cepa (onions), Lactuca sativa (lettuce), Daucus carota (carrots), Solanum lycopersicum (tomatoes), as well as fruits such as Passiflora edulis (passion fruit), Carica papaya (papaya). Composting was run over a period of 90 days. We then measured several bromatological analyses of compost. For phytotoxicity tests of compost relative seed germination (RSG), relative radicle growth (RRG) and Germination Index GI on L. sativa were measured. Results: The prepared compost showed the following parameters: pH (8.6), OM (21.4%), C/N (11.59), EC (7.24 dS/m), Total N (1.72%), P (325.6 ppm), Al (0.1 cmol.kg−1) K (41 cmol.kg−1), Ca (8.12 cmol.kg−1), Mg (5.62 cmol.kg−1), Na (0.76 cmol.kg−1). Minor elements appeared in acceptable ranges, and do not pose any risk. Besides, the compost showed a germination rate of 112.6% on L. sativa, which allowed us to validate its high maturity. Conclusion: The compost produced stands out for its quality and efficiency, due to its low phytotoxicity, specific mixture of the materials and the processing method. The mature compost produced represents a valuable material for the acidic and nutrient-poor soils of the Colombian Piedmont.